A Nanobody-Based Toolset to Monitor and Modify the Mitochondrial GTPase Miro1 - Fagbadebo, Funmilayo O.; Kaiser, Philipp D.; Zittlau, Katharina; Bartlick, Natascha; Wagner, Teresa R.; Froehlich, Theresa; Jarjour, Grace; Nueske, Stefan; Scholz, Armin; Traenkle, Bjoern; Macek, Boris; Rothbauer, Ulrich (Frontiers in Molecular Biosciences, 2022)
The mitochondrial outer membrane (MOM)-anchored GTPase Miro1, is a central player in mitochondrial transport and homeostasis. The dysregulation of Miro1 in amyotrophic lateral sclerosis (ALS) and Parkinson's disease (PD) suggests that Miro1 may be a potential biomarker or drug target in neuronal disorders. However, the molecular functionality of Miro1 under (patho-) physiological conditions is poorly known. For a more comprehensive understanding of the molecular functions of Miro1, we have developed Miro1-specific nanobodies (Nbs) as novel research tools. We identified seven Nbs that bind either the N- or C-terminal GTPase domain of Miro1 and demonstrate their application as research tools for proteomic and imaging approaches. To visualize the dynamics of Miro1 in real time, we selected intracellularly functional Nbs, which we reformatted into chromobodies (Cbs) for time-lapse imaging of Miro1. By genetic fusion to an Fbox domain, these Nbs were further converted into Miro1-specific degrons and applied for targeted degradation of Miro1 in live cells. In summary, this study presents a collection of novel Nbs that serve as a toolkit for advanced biochemical and intracellular studies and modulations of Miro1, thereby contributing to the understanding of the functional role of Miro1 in disease-derived model systems.